2020
DOI: 10.1080/0167482x.2020.1729118
|View full text |Cite
|
Sign up to set email alerts
|

Testing the birth attitude profile scale in a Swedish sample of women with fear of birth

Abstract: Objective: The aim of this study was to explore the "Birth Attitude Profile Scale (BAPS)" in a selected sample of women with fear of birth. Another aim was to develop profiles of women according to their birth attitudes and levels of childbirth fear in relation to background characteristics. Methods: A secondary analysis of data collected in two different samples of women with fear of birth. Data were collected by a questionnaire in gestational week 36 and background data from mid-pregnancy. A principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…In the form prepared by the researcher in accordance with the literature, there are 22 items in total: 11 items about the socio-demographic characteristics of women (age, height, weight, educational status, marital status, employment status, income level perception, income level, place of residence, family structure, and smoking status); 5 items about obstetric characteristics (gestational week, history of abortion-curettage, status of wanted pregnancy, status of receiving regular prenatal care, the source of care); and, 6 items about preparation for childbirth (status of receiving birth preparation education, source of birth preparation education, status of being ready to become a mother, status of receiving spousal support during pregnancy, status of receiving support from family or friends during pregnancy, and satisfaction with pregnancy) [19,36,39].…”
Section: Personal Information Formmentioning
confidence: 99%
“…In the form prepared by the researcher in accordance with the literature, there are 22 items in total: 11 items about the socio-demographic characteristics of women (age, height, weight, educational status, marital status, employment status, income level perception, income level, place of residence, family structure, and smoking status); 5 items about obstetric characteristics (gestational week, history of abortion-curettage, status of wanted pregnancy, status of receiving regular prenatal care, the source of care); and, 6 items about preparation for childbirth (status of receiving birth preparation education, source of birth preparation education, status of being ready to become a mother, status of receiving spousal support during pregnancy, status of receiving support from family or friends during pregnancy, and satisfaction with pregnancy) [19,36,39].…”
Section: Personal Information Formmentioning
confidence: 99%
“…In addition, spousal support was found to be a mediator variable in the relationship between self-efficacy and FOC, showing the importance of support as a buffer against stressful situations such as a delivery. A Swedish study of pregnant women with FOC revealed two clusters: one with strong attitudes and lower fear, labeled "self-determiners", and one with no strong attitudes but high levels of fear, labeled "fearful" [7]. It seems important to differentiate between the different subtypes of women with FOC to determine which treatment would be most effective.…”
Section: Editorialmentioning
confidence: 99%
“…Labour is an important period in women's lives, but it is also a great source of stress for them (Hildingsson & Rubertsson, 2021). Fear of childbirth can range from mild anxiety and fear to severe fear (Dencker et al, 2019;Nilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%